A compact jet array impingement cooling system driven by integrated piezoelectric micropump. (15th May 2023) - Fan, Yiwen; Zhang, Xinfeng; Xiang, Linyi; Cheng, Yanhua; Luo, Xiaobing
Highlights: A compact jet array impingement cooling system driven by integrated piezoelectric micropump is proposed. The maximum convective heat transfer coefficient h  = 20572 W/m 2 ·K is achieved at a heat flux of 91.5 W/cm 2 . A low electric power consumption of 0.023 w is achieved under a heat load of 200 w (50 W/cm 2 ). The transient heat transfer process of the piezo-driven jet impingement cooling is studied. Abstract: Thermal management has become a bottleneck for high-power electronics due to high heat flux. Liquid cooling has been developed as an effective way to dissipate the heat of electronic devices. However, the existing liquid cooling systems are mostly too bulky to be applied in the miniaturized devices with very limited installation space. In this work, by integrating jet impingement cooling with piezoelectric micropump, we proposed a compact liquid cooling system that simultaneously enables high heat removal capability and tiny volume. The functions of jet array impingement cooling and coolant pumping are realized in a single component with an external dimension of 40 mm × 40 mm × 10 mm. The thermal performance of the system was investigated by experiments. The results show that the convective heat transfer coefficient achieves 20572 W· m −2 · K −1 at a heat flux of 91.5 W/cm 2 . And the electric power consumption of the system is only 0.023 W under a heat load of 200 W (50 W/cm 2 ). Simulations, which agree well with experiments, were further employed to study the transient heat transport process. This novel jet impingement cooling system driven by integrated piezoelectric micropump is compact and efficient, which provides a promising solution for the thermal management of high-power, miniaturized electronic devices.